User-side Cloud Energy Storage Locating and Capacity Configuration - Ma, Yongji; Cao, Fen; Zhou, Zhihang; Yang, Anyuan; Wang, Huifang (2023 IEEE 7th Conference on Energy Internet and Energy System Integration (EI2), 2023)
Under the background of new power system, economic and effective utilization of energy storage to realize power storage and controllable transfer is an effective way to enhance the new energy consumption and maintain the stability of power system. In this paper, a cloud energy storage(CES) model is proposed, which firstly establishes a wind- PV -load time series model based LHS and K-medoids to complete the scenario generation and reduction. MOPSO algorithm is used to achieve the centralized energy storage configuration with voltage, load volatility, and the total cost of social energy use as the indexes. Afterwards, a segmented model is suggested on this basis to realize CES day-ahead scheduling. Eventually, based on the Shapley value, the revenue settlement of users within the cloud is accomplished. The simulated CES model enables the cooperative call of multiple energy storage, which is sufficiently organized and balances the benefits of each subject to ensure the sustainable development of the model.